Prevalence and Risk Factors of Congenital Hearing Loss in Turkey: A Systematic Review - Sokmen, Yasemin; Odabas, Resmiye Kaya; Taspinar, Ayten (Springer Publishing Co, 2025)
Congenital hearing loss hinders the child's social, emotional, and intellectual development. This systematic review was planned because the determination of congenital hearing loss and risk factors will guide health service planning. This systematic review was conducted based on previous studies in Turkey to determine the prevalence and the risk factors of newborn congenital hearing loss. This systematic review was conducted between November 2020 and February 2021; Google Scholar, PubMed, ScienceDirect, EBSCOhost, and Springer electronic databases were screened with the keywords "newborn hearing screening" and "congenital hearing loss." According to the results of the systematic review of 13 studies, 1 prospective and 12 retrospective, the prevalence of congenital hearing loss is 0.5% and 1.1% in those with risk factors; newborns are screened within 1 month, diagnosed within 2 months on average, and intervened with between the 3rd and 14th months; and the most common risk factors for hearing loss are admission in intensive care/mechanical ventilation for more than 5 days/history of ototoxic drug use, hyperbilirubinemia requiring an exchange transfusion/ phototherapy, prematurity, consanguineous marriage, and family history of hearing loss, respectively.
Keywords: Newborn Hearing Screening; Congenital Hearing Loss; Systematic Review; Turkey; Developmental Care; Assessment